Impact of bone metastasis on prognosis in non-small cell lung cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Zhu, Yonghua; She, Jingyao; Sun, Rong; Yan, XinXin; Huang, Xinyao; Wang, Peijuan (Frontiers in Immunology, 2024)
BackgroundLung cancer is a leading cause of cancer-related deaths globally, with non-small cell lung cancer (NSCLC) accounting for approximately 85% of cases. While immune checkpoint inhibitors (ICIs) have transformed treatment for advanced NSCLC, the role of bone metastasis in modulating ICI efficacy remains unclear. Bone metastasis, occurring in 30-40% of advanced NSCLC cases, is associated with worse outcomes. However, how this affects the therapeutic benefit of ICIs has not been fully elucidated, highlighting a critical knowledge gap in optimizing treatment for this patient population.MethodsA comprehensive literature search across multiple databases, including PubMed, Embase, and Cochrane, identified 13 studies with a total of 3,681 patients, of whom 37.6% had bone metastasis. Overall survival (OS) and progression-free survival (PFS) were compared between NSCLC patients with and without bone metastasis. Data were analyzed using a random-effects model to account for study heterogeneity.ResultsThe meta-analysis demonstrated that bone metastasis significantly worsened overall survival (OS) and progression-free survival (PFS) in NSCLC patients treated with ICIs. Specifically, bone metastasis was associated with a 45% increased risk of death (HR: 1.45, 95% CI: 1.30–1.62, p < 0.001) and a 40% increased risk of disease progression (HR: 1.40, 95% CI: 1.25–1.58, p < 0.001). No statistically significant impact on PFS was observed. (HR: 1.28, 95% CI: 0.77–2.10, p = 0.34). High heterogeneity was observed in some subgroup analyses (I² = 72%), indicating variability in the results.ConclusionBone metastasis is a significant negative prognostic factor for NSCLC patients treated with ICIs, associated with a higher risk of mortality and disease progression. These results underscore the importance of tailored treatment approaches for NSCLC patients with bone metastasis and call for further research to optimize therapy outcomes in this group.